Antioxidants and Oxidative Stress: Focus in Obese Pregnancies - Alcala, Martin; Gutierrez-Vega, Sebastián; Castro, Erica; Guzman-Gutiérrez, Enrique; Ramos-Álvarez, Maria Pilar; Viana, Marta (Frontiers in Physiology, 2018)
The prevalence of obesity in women of childbearing age around the globe has dramatically increased in the last decades. Obesity is characterized by a low-state chronic inflammation, metabolism impairment and oxidative stress, among other pathological changes. Getting pregnant in this situation involves that gestation will occur in an unhealthy environment, that can potentially jeopardize both maternal and fetal health. In this review, we analyze the role of maternal obesity-induced oxidative stress as a risk factor to develop adverse outcomes during gestation, including reduced fertility, spontaneous abortion, teratogenesis, preeclampsia and intrauterine growth restriction. Evidences of macromolecule oxidation increase in reactive oxygen species generation and antioxidant defense alterations are commonly described in maternal and fetal tissues. Thus, antioxidant supplementation become an interesting prophylactic and therapeutic tool, that yields positive results in cellular and animal models. However, the results from most meta-analysis studying the effect of these therapies in complicated gestations in humans are not really encouraging. It is still to be analyzed whether these therapies could work if applied to cohorts of patients at a high risk, such as those with low concentration of antioxidants or obese pregnant women.